Testing experimental devices in the extension piece to increase the selectivity of bottom trawl in the Nw Mediterranean - Mario Sbrana; Francesco De Carlo; Alessandro Ligas; Andrea Massaro; Claudia Musumeci; Ilaria Rossetti; Marina Sartini; Claudio Vasapollo; Claudio Viva; Paolo Sartor; Carlo Pretti (Frontiers in Marine Science, 2022)
In the Mediterranean, experiments and technical measures aimed at improving the selectivity of bottom trawl nets mostly concern modifications to the codend. Grids have been tested in various areas, but have not been adopted for management purposes so far. The present study aims to evaluate whether the adoption of diamond meshes turned by 90° (T90 configuration) and a selection grid with 2 cm bar spacing, both placed in the extension piece of a commercial bottom trawl net, can contribute in reducing the capture of specimens under the Minimum Conservation Reference Size (MCRS) for the main commercial species. The results indicated that the T90 configuration has no effect compared to the commercial net commonly used by fishers. The grid showed a reduction of the catches of European hake individuals between 11 and 19 cm Total Length (TL). However, the use of this device reduced the catch of many species, such as red mullet, deep-water rose shrimp and broad tail short fin squid. This reduction was observed also for specimens above MCRS. In conclusion, the T90 applied to the extension piece does not provide any improvement in selectivity, contrary to what has been observed when the T90 is placed at the codend. In contrast, the grid could be a possible way to increase selectivity. However, the use of grid should be further investigated to identify settings that can avoid the loss of a substantial fraction of commercial catch.